Trycktampong efter mastektomi : en metod för att minska andelen sårkomplikationer? - Bylin, Jonas (SLU/Dept. of Animal Environment and Health (until 231231), 2006)
Mammary gland neoplasia is one of the most common diseases in the bitch and the most common neoplastic disease. More than 13 % of the female dog population in Sweden suffers from mammary tumors during their lifetime. The disease can affect bitches in all ages but most often middle aged and older dogs. Some breeds such as Poodle and English Setter are predisposed for the disease.